WORKING WITH HYPERACTIVE CHILDREN IN EDUCATION: PEDAGOGICAL APPROACHES, PROBLEMS AND PRACTICAL SOLUTIONS - Ibrohimova Fotima Qobiljon kizi (Bright Mind Publishing, 2025)
This article systematically analyzes the pedagogical aspects of working with hyperactive children (students with ADHD symptoms) in the educational process, their psychological characteristics, problems encountered in the process of adaptation to educational activities, and practical solutions. The study processed the data obtained on the basis of observation, experimental-methodological methods, interviews, and questionnaires, and studied the impact of effective pedagogical strategies - short and structured tasks, positive stimulation, sensory aids, and active breaks on the educational process. The results showed the high effectiveness of integrated approaches in managing the attention of hyperactive children, forming behavioral stability, and increasing learning motivation. This article provides scientific and practical recommendations for educators, psychologists, and parents aimed at optimizing work with hyperactive students.
Keywords: Hyperactive child, ADHD, educational process, pedagogical approach, impulsivity, attention deficit, positive stimulation, sensory aids, motor break, behavior management, individual approach, educational effectiveness.